2004
DOI: 10.1105/tpc.104.027466
|View full text |Cite
|
Sign up to set email alerts
|

FRAGILE FIBER3, an Arabidopsis Gene Encoding a Type II Inositol Polyphosphate 5-Phosphatase, Is Required for Secondary Wall Synthesis and Actin Organization in Fiber Cells

Abstract: Type II inositol polyphosphate 5-phosphatases (5PTases) in yeast and animals have been known to regulate the level of phosphoinositides and thereby influence various cellular activities, such as vesicle trafficking and actin organization. In plants, little is known about the phosphatases involved in hydrolysis of phosphoinositides, and roles of type II 5PTases in plant cellular functions have not yet been characterized. In this study, we demonstrate that the FRAGILE FIBER3 (FRA3) gene of Arabidopsis thaliana, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(89 citation statements)
references
References 42 publications
5
84
0
Order By: Relevance
“…Various studies in Arabidopsis have identified at least three putative PI(3)P phosphatases and no PI(3) kinases that may use or generate PI(3,4)P 2 (Gillaspy, 2009;Lee et al, 2009). Sequence analyses have also led to the identification of 16 putative PI(5)P phosphatases and four putative PI(5) kinases that may use or generate PI(4,5)P 2 ( Mueller-Roeber and Pical, 2002;Zhong et al, 2004;Gillaspy, 2009). Additionally, there are other potential ways that PI(4)P levels could be modulated, including lipid hydrolysis and lipid transfer between membranes or membrane bilayers, but again little is known about these processes .…”
Section: Discussionmentioning
confidence: 99%
“…Various studies in Arabidopsis have identified at least three putative PI(3)P phosphatases and no PI(3) kinases that may use or generate PI(3,4)P 2 (Gillaspy, 2009;Lee et al, 2009). Sequence analyses have also led to the identification of 16 putative PI(5)P phosphatases and four putative PI(5) kinases that may use or generate PI(4,5)P 2 ( Mueller-Roeber and Pical, 2002;Zhong et al, 2004;Gillaspy, 2009). Additionally, there are other potential ways that PI(4)P levels could be modulated, including lipid hydrolysis and lipid transfer between membranes or membrane bilayers, but again little is known about these processes .…”
Section: Discussionmentioning
confidence: 99%
“…For this work, we used a purified bovine Ins (1,4,5)P 3 receptor in radiolabeled competition binding assays that are well established and used by several plant laboratories (Carland and Nelson, 2004;Zhong et al, 2004;Gunesekera et al, 2007;Perera et al, 2008). We found no differences, with 19-d-old wild-type plants having 404 6 50 pg Ins(1,4,5)P 3 /g tissue and 19-d-old mips1-2 plants having 463 6 91 pg Ins(1,4,5)P 3 /g tissue.…”
Section: Mips1 Impacts Inositol Synthesismentioning
confidence: 99%
“…Other examples of actin's involvement in cell wall synthesis and cell elongation come from members of the fragile fiber ( fra) family of mutants [46][47][48]. Cell walls in the fiber cells of fra4 (also known as root hair defective 3) are abnormally thin, have altered composition and reduced mechanical strength, and have reduced cell elongation in all organs [46].…”
Section: Other Examples Of Actin's Role In Directional Cell Expansionmentioning
confidence: 99%
“…FRA4 encodes a novel protein that has putative GTPbinding motifs [46]. FRA3 encodes an inositol polyphosphate phosphatase and FRA7 encodes a so-called 'suppressor of actin (SAC) domain' phosphatase, which is also active against inositol polyphosphates [47,48]. Both also appear to be necessary for normal actin organization and secondary cell wall formation, with fra7 mutant plants having reduced expansion in most, if not all, organs [48].…”
Section: Other Examples Of Actin's Role In Directional Cell Expansionmentioning
confidence: 99%